Rivaroxaban and macitentan can be coadministered without dose adjustment but the combination of rivaroxaban and St John's wort should be avoided - Huppertz, Andrea; Werntz, Lars; Meid, Andreas; Foerster, Kathrin; Burhenne, Jürgen; Czock, David; Mikus, Gerd; Haefeli, Walter E. (British journal of clinical pharmacology, 2018)
Aims We assessed the potential mutual interaction of oral macitentan (cytochrome P450 (CYP) 3A4 substrate) at steady-state with single-dose oral rivaroxaban (CYP3A4 and P-glycoprotein substrate) and evaluated the effect of the CYP3A and P-glycoprotein inducer St John's wort (SJW) on the pharmacokinetics of these drugs in healthy volunteers. Methods Twelve healthy volunteers completed this open-label, monocentre, two-period, one-sequence phase I clinical trial. The pharmacokinetics of macitentan (10 mg) was assessed on study days 3 (single dose), 15 (steady-state), 16 (impact of rivaroxaban) and 29 (after induction by oral SJW), and of rivaroxaban on days 2 (single dose), 16 (impact of macitentan at steady-state) and 29 (after induction by SJW). Concurrently, we quantified changes of CYP3A activity using oral microdoses of midazolam (30 μg). Results Rivaroxaban and macitentan did not significantly change the pharmacokinetics of each other. After induction with SJW, CYP3A activity increased by 272% and geometric mean ratios of macitentan AUC decreased by 48% and of Cmax by 45%. Concurrently, also geometric mean ratios of rivaroxaban AUC and Cmax decreased by 25%. Conclusions There is no evidence for a relevant pharmacokinetic interaction between macitentan and rivaroxaban suggesting that these two drugs can be combined without dose adjustment. SJW strongly increased CYP3A activity and substantially reduced rivaroxaban and macitentan exposure while estimated net endothelin antagonism only decreased by 20%, which is considered clinically irrelevant. The combination of SJW with rivaroxaban should be avoided.